Identification of potential mycotoxin producing fungi on agricultural products in Hungary and Serbia - Baranyi, Nikolett; Kocsubé, Sándor; Kiss, Noémi; Palágyi, Andrea; Varga, Mónika; Tóth, Beáta; Varga, János (Acta Biologica Szegediensis, 2014)
One of the most important effects of climate change is the occurrence of thermotolerant mycotoxin producing fungi in countries with temperate climate, causing mycotoxin contamination of agricultural products. Indeed, a shift has recently been observed in the occurrence of aflatoxin producing fungi in Europe, with consequent aflatoxin contamination in agricultural commodities including maize and milk in several European countries including Serbia, Croatia, Slovenia, Romania and Ukraine. These observations led us to examine the occurrence of mycotoxin producing Aspergilli in agricultural products in Hungary and Serbia. The samples were collected from cereal fields in Hungary and North-Serbia (Vojvodina) after harvest in 2012. Surface-sterilized cereal seeds were placed on selective media and the isolated fungal strains were identified using morphological methods. The species identification of selected isolates was carried out using sequence-based methods. Several potentially aflatoxigenic A. flavus isolates were identified on maize. Further examinations of mycotoxin producing abilities of the isolates, and their occurrence in milk and milk-derived products are in progress.